1999
DOI: 10.1016/s0006-3495(99)77084-0
|View full text |Cite
|
Sign up to set email alerts
|

The Conduction of Protons in Different Stereoisomers of Dioxolane-Linked Gramicidin A Channels

Abstract: Two different stereoisomers of the dioxolane-linked gramicidin A (gA) channels were individually synthesized (the SS and RR dimers;. Science. 244:813-817). The structural differences between these dimers arise from different chiralities within the dioxolane linker. The SS dimer mimics the helicity and the inter- and intramolecular hydrogen bonding of the monomer-monomer association of gA's. In contrast, there is a significant disruption of the helicity and hydrogen bonding pattern of the ion channel in the RR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(102 citation statements)
references
References 38 publications
3
98
1
Order By: Relevance
“…These findings explicitly indicate that the aforementioned inclusion complexes are excellent models for the elucidation of principal forces, dynamic properties and charge transport mechanisms in the water clusters of biological systems (10)(11)(12)(13)(14), in the building blocks of many polyiodide materials (15) and in the cyclodextrin complex formation processes (16,17). Despite the fact that the individual nature of each counterion appears 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 The temperature variation was controlled with a Ventacon Winchester instrument equipped with a CALCOMMS 3300 autotune controller.…”
Section: Introductionmentioning
confidence: 71%
“…These findings explicitly indicate that the aforementioned inclusion complexes are excellent models for the elucidation of principal forces, dynamic properties and charge transport mechanisms in the water clusters of biological systems (10)(11)(12)(13)(14), in the building blocks of many polyiodide materials (15) and in the cyclodextrin complex formation processes (16,17). Despite the fact that the individual nature of each counterion appears 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 The temperature variation was controlled with a Ventacon Winchester instrument equipped with a CALCOMMS 3300 autotune controller.…”
Section: Introductionmentioning
confidence: 71%
“…This result suggests that an analysis of water permeation through gramicidin which refers only to this one degree of freedom would be appropriate. However, the number of essential coordinates required to describe the permeation process is likely to increase as the channel environment is made more complex (13,15) or as the pore radius increases (32). The development of numerical methods for constructing framework models would then be required to apply this approach to the description of these more complex molecular motions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…If the movements of the center of charge and of the defects are substantially independent, two or more degrees of freedom may be required to describe their interaction. A second example is provided by the RR dioxolane linked analogs of gramicidin (12)(13)(14). Molecular modeling suggests that the backbone carbonyls closest to the dimer interface can flip between orientations of almost equal energy, one projecting at an angle of 20-30° into the pore and the other projecting at an angle of 20-30° away from the pore (15).…”
Section: Introductionmentioning
confidence: 99%
“…The permeation of protons in gA channels does not seem to occur via hydrodynamic diffusion of protonated waters. Instead, an H 1 transfer Grotthuss-type mechanism may occur in various gA channels (5,6,(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, proton transfer can be measured in a single channel molecule. Recent work from our laboratory (10)(11)(12)16,(22)(23)(24) have used the SS and RR diastereoisomers of dioxolane-linked gA channels (16,25) to measure H 1 transfer in water wires, and to correlate those experimental measurements with possible molecular mechanisms (16,26). It was suggested that the chiral centers of the dioxolane linker underlie the profound quantitative and qualitative differences in the rate of H 1 transfer in distinct gA channels.…”
Section: Introductionmentioning
confidence: 99%